TOURISM DEVELOPMENT MODEL FOR TRADITIONAL SPA IN SURAKARTA CITY, INDONESIA - Deria Adi Wijaya; Amad Saeroji (Jurnal Inovasi Penelitian, 2022)
This article discusses the potential and model to develop the traditional spa packages in Surakarta City, Indonesia. The general purpose is to present a model of tourism development for traditional spa that is relevant to stakeholders such as, spa businesses, local goverment, tourism business, including tourists. The specific objectives are; (1) to identify potential of traditional spa in Surakarta, (2) to create a map of traditional spa per districts, (3) to design the tour pakages model of traditional spa in Surakarta City. This research used a descriptive - qualitative research methods to find information on tourism development model of traditional spa in Surakarta city. Data were collected using the participatory observation, interviews and literature studies. Data collection with Participatory observation and interviews were conducted in several government agencies and spa businesses, massages, and traditional body care throughout the city. The literature study covered all the concepts and theories associated with traditional spa tourism especially references to traditional spa business in Surakarta city. The results yielded map of traditional spa tourism for each district, which shows that the potential of traditional spa in Surakarta city is very diverse. Based on that, a decent spa tour package can be designed. The package shall deserves to be a new concept for developing model of spa tour and wellness in Surakarta city. Also, further research on climate change impact on spa tourism business will be necessary.